(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This scientific article examines the characteristics of age groups learning English. The main features inherent in each group are revealed. This approach helps the teacher to create an effective plan for working with his students to achieve a successful result.